The Effect of Experienced Incivility From Supervisor and Coworkers Towards Instigated Incivility in Daily Level Among Nurses - Verasari, Metty; Hamzah, Hazalizah (Universitas Malikussaleh, 2019)
Workplace Incivility is a common phenomenon in workplaces in many organisation. Understanding the concept of workplace incivility to hospital managers and other health care organizations. The necessary antecedent of workplace incivility consisted of the presence of two or more people, with one or more as the source of the incivility, and another or others as its target in the workplace. This study aimed to understand the effect of experienced incivility from nurses supervisor and coworker in hospital. Its also try to figure out instigated incivility pattern in daily level. The methodology to analyze is diary study between 3 days on 102 nurses ini Sumatra, Indonesia. Results of this study indicate a differences in the effect of experienced incivility on instigated incivility in terms of measurements per days. Simultaneously experienced incivility by supervisors and coworkers has an influence on instigated incivility in the first day, and second day from suprevisor incivility, but on experienced incivility from coworkers influenced in second day, and third day to instigated incivility.